Cocombustion of Coal–Water Fuel with Fuel Oil; Journal of Energy Engineering; Vol. 150, iss. 3 - Gvozdyakov D. V. Dmitry Vasilievich; Zenkov A. V. Andrey Viktorovich; Kaltaev A. Albert; Shuataev M. K. Merlan Kalkamanovich (2024, 2024)
Title screen